2002
DOI: 10.2190/lv5g-e3jv-6cvt-fkn5
|View full text |Cite
|
Sign up to set email alerts
|

Psychomanteum Research: Experiences and Effects on Bereavement

Abstract: A Psychomanteum Process involving mirror-gazing was conducted in a research setting to explore apparent facilitated contact with deceased friends and relatives, and to collect data on the phenomena, experiences, and effects on bereavement. A pilot study with five participants resulted in strong experiences and four apparent contacts. The main study took 27 participants through a three-stage process: remembering a deceased friend or relative, sitting in a darkened room gazing into a mirror while thinking of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 7 publications
3
21
0
Order By: Relevance
“…With lower power, results by follow up somewhat parallel Hastings et al (2002) andHastings (2012a). Studies share reductions in items pertaining to sadness, loss, anger, fear, and loneliness.…”
Section: International Journal Of Transpersonal Studies 15supporting
confidence: 54%
See 2 more Smart Citations
“…With lower power, results by follow up somewhat parallel Hastings et al (2002) andHastings (2012a). Studies share reductions in items pertaining to sadness, loss, anger, fear, and loneliness.…”
Section: International Journal Of Transpersonal Studies 15supporting
confidence: 54%
“…Many of Moody's (1992) 25 volunteers reported the healing and "smoothing over" (p. 113) of relationships as a result of discussing their lost loved one and sitting in a darkened, private enclosure; 12 experienced visions of the deceased and did not cognitively question the validity of the unusual sensory perceptions or eidetic imagery seen in and around the mirror. Research on elements that comprise the process, including scrying-an ancient information-accessing technique involving gazing into a reflective surface (Besterman, 1924(Besterman, /2005)-sensory deprivation (Bood, Sundequist, Kjellgren, Nordstrom, & Norlander, 2007;van Dierendonck & te Nijenhuis, 2005), and meditation (Lane, Seskevich, & Pieper, 2007;Manocha, Black, Sarris, & Stough, 2011) helps to explain the effects found during subsequent psychomanteum research (e.g., Arcangel, 1997;Radin & Rebman, 1996) to Moody's (1992) initial exploration, but it was Roll (2004), Hastings et al (2002), and Hastings (2012a) who directly investigated the psychomanteum's impact on psychological stress and painful emotions in the context of bereavement. Roll (2004) led 57 participants through a process involving a psychomanteum chamber and structured day of activities, including conversations about the deceased and a relaxing nature walk.…”
Section: International Journal Of Transpersonal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even those participants who did not experience contact reported significant improvements in feelings of grief and sadness and the need to communicate (Hastings et al, 2002). As a whole, participants also reported significant alterations in unresolved feelings, missing the person, and feelings of grief, loss, sadness, guilt, and fear (Hastings et al, 2002).…”
Section: Alternative Experiences and Interventionsmentioning
confidence: 99%
“…These techniques often involve long periods of time gazing into a mirror in a very structured environment. Statistical analysis in one study involving mirror gazing and bereavement indicated that there were strong self-reported shifts in unresolved feelings involving resolution, healing, and comfort (Hastings et al, 2002). The intent of Cushnir's (2005) mirror gazing exercise however, is not to resolve feelings of guilt or discomfort, but to offer ways of reintroducing one to self, to allow hidden thoughts to surface, and in so doing, learning to appreciate the now.…”
Section: Mirror Gazingmentioning
confidence: 99%